PENATALAKSANAAN FISIOTERAPI PADA ANAK KONDISI TORTIKOLIS KONGENITAL DENGAN MYOFASCIAL RELEASE TEKNIK (MFRT) DAN TERAPI LATIHAN - Aida Naurah Septi; Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2020)
Congenital Torticollis is a deformity in the position of the head caused by muscle stiffnes on one side that causes limited neck movement to the side that experiences stiffness. The physiotherapy problem is are spasms, decreased muscle strength, shortening of muscle length, limited range motion and decreased functional activity.  The physiotherapy examination includes examination of spasms, muscle stength, muscle length, range of motion, functional activit. Intervention technology is Myofascial Release Technique (MFRT) and Exercise Therapy. The purpose of study to determine the effect of physiotherapy management in condition Congenital Torticollis with Myofascial Release Techniques (MFRT) and Exercise Therapy. This research conducted in YPAC Surakarta with descriptive analytic research design with study design. Subjects patients Congenital Torticollis with Myofascial Release Technique (MFRT) and Exercise Therapy physiotherapy interventions. The data collection method of the heteroanamnesis method. Research instruments in the form of examination of spasm with palpasi, muscle strength with XOTR, muscle length with midline, ROM with goneometer and functional activity with Toronto Western Spasmodic Torticollis Ranting Scale (TWSTRS). Based on the results of the therapy as follows : (1)  there is a decrease in spasm T1=1 become T5=0 (2) increased muscle strength T1=T become T5=X (3) increased muscle length T1=3cm become T5=4 cm (4) increased range of motion cervical flexion motion T1=40° become T5=45°, extension T1=40° become T5=45°, lateral fleksi dekstra T1=35° become T5=45°, lateral fleksi sinistra T1=30° become T5=40°, rotasi dekstra T1=30° become T5=35°, rotasi sinistra T1=60° become T5=60° (5) increased daily functional activity. The research conclusion that physiotherapy interventions with Myofascial Release Technique (MFRT) and Exercise Therapy can reduce problem that arise in Congenital Torticollis condition.